A Dicer2 from Scylla paramamosain activates JAK/STAT signaling pathway to restrain mud crab reovirus. (February 2022) - Deng, Hengwei; Xian, Danrong; Lian, Taixin; He, Mingyu; Li, Jingjing; Xu, Xiaopeng; Guo, Zhixun; He, Jianguo; Weng, Shaoping
Abstract: A Dicer2 gene from Scylla paramamosain, named SpDicer2, was cloned and characterized. The full length of SpDicer2 mRNA contains a 121 bp 5'untranslated region (UTR), an open reading frame (ORF) of 4518 bp and a 3′ UTR of 850 bp. The Sp Dicer2 protein contains seven characteristic Dicer domains and showed 34%–65% identity and 54%–79% similarity to other Dicer protein domains, respectively. The mRNA of SpDicer2 was high expressed in hemocytes, intestine and gill and low expressed in the eyestalk and muscle. Moreover, expression of SpDicer2 was significantly responsive to challenges by mud crab reovirus (MCRV), Poly(I:C), LPS, Staphylococcus aureus and Vibrio parahaemolyticus . Sp Dicer2 was dispersedly presented in the cytoplasm except for a small amount in the nucleus. Sp Dicer2 could activate Sp STAT to translocate from the cytoplasm to the nucleus, and significantly increase the transcription activity of the wsv069 promoter, suggesting that Sp Dicer2 activated the JAK/STAT pathway. Furthermore, silencing of SpDicer2 in vivo increased the mortality of MCRV infected mud crab and the viral load in tissues and down-regulated the expression of multiple components of Toll, IMD and JAK-STAT pathways and almost all the examined immune effector genes. These results suggested that Sp Dicer2 could play an important role in defense against MCRV via activating the JAK/STAT signaling pathways in mud crab. Highlights: The full length of a Dicer2 gene from Scylla paramamosain ( SpDicer2 ) was cloned and characterized. The expression of Sp Dicer2 was significantly upregulated by stimulation with mud crab reovirus (MCRV), poly(I:C) and LPS. Sp Dicer2 could activate the JAK/STAT pathway in S. paramamosain. Sp Dicer2 could play an important role in defense against MCRV in mud crab.